Mães trabalhadoras: um estudo quanti-qualitativo sobre uso do tempo em papéis ocupacionais, poder aquisitivo e satisfação com a vida - Barbano, Leticia Maria (2020)
Today, the reconciliation of work and family is a crucial issue, being especially difficult for women to balance these two aspects. Anchored in the Model of Human Occupation, this research aimed to compare and describe the time use, occupational roles, purchasing power and satisfaction with the lives of part-time and full-time working mothers. Following a statistical sample with 95% reliability and 5% margin of error, 800 working mothers from different regions of Brazil were participants in this research. Data were gathered through an online survey, and the following instruments were applied: Role Checklist, Brazil Economic Classification Criterion (CCEB), Life Satisfaction Scale (SWLS), socioeconomic questionnaire, with an open question about the worker role. Quantitative data were analyzed using Multiple Correspondence Analysis, T-Student Test and Pearson Correlation. Qualitative data were analyzed using thematic content analysis. Quantitative results showed that full-time working mothers had higher purchasing power, as well as chances of greater satisfaction with their life (p = 0.307). There was an association between purchasing power and life satisfaction and educational level and life satisfaction. Full-time working mothers spent more time to the family member role (p = 0.001) and caregiver role (p = 0.000) than part-time working mothers. The qualitative results were grouped into three categories (Time Use; Labor Market; Brazilian Culture on Working Women) and nine subcategories (Role Overload and Double Journey; Self Care and Leisure; Family Time; Role Balance; Prejudice by being a mother; Journey and work environment; Support networks; Partner/ spouse assistance; Feelings and perceptions). The conclusion is that full-time mothers can have higher satisfaction with life and can spend more time working and with their families, and less time for domestic tasks. Qualitative data showed that the support network is an important factor for the reconciliation of occupational roles for these mothers; regardless if is a part-time or a full-time job.